Bitemporal scalp, lip and tongue necrosis in giant cell arteritis: A rare presentation - Rajesh Kumar; Hemant Gupta; Anil Jadhav; S V Khadilkar (Wolters Kluwer Medknow Publications, 2013)
A 74-year-old man was presented with fever, bilateral throbbing temporoparietal headache, jaw claudication, and bilateral loss of vision. On examination, he had bilateral scalp necrosis with impending necrosis of lip and tongue. Temporal artery biopsy was done, and it was compatible with active temporal arteritis. This is one of the rare presentations of giant cell arteritis where there is simultaneous necrosis of scalp, lip, and tongue, and to the best of our knowledge, it is the first case reported from India.